Editorial Preface - Ibrahim, Nabilah; Yunus, Riduan (International Journal of Integrated Engineering, 2019)
It is a pleasure to present the first special issue of mechanical engineering for the year 2019. All manuscripts received by the editors were examined by referees instructed to evaluate the papers by the significance and novelty. There are 30 papers published in this issue came from various countries such as Malaysia, Indonesia, Japan, Thailand and industry. Most of the papers discussed in the aspect of mechanical engineerings such as welding technology, computational fluid dynamic, materials and industrial engineering. Many thanks to all contributors and reviewers for their participation in making this issue can be realized.